Insurance Awareness of the Customers in Poland - Ratowska-Dziobiak, Eleonora (Journal of Finance and Financial Law, 2016)
The aim of the article is the analysis of the changes in the insurance awareness of consumers on the Polish market. Focus and expert interviews indicate that clients appreciate the comprehensive service. According to the speakers, taking into account new threats, adjustment of the offer to the needs of the buyer, as well as the introduction of innovative distribution channels, significantly influence the demand for the insurance services.